Spectrophotometric Determination of Celecoxib in Pharmaceutical Preparations (Journal of the College of Basic Education, 2022)
Two simple and sensitive spectrophotometric methods have been developed for the estimation of Celecoxib in pure and pharmaceutical dosage forms. Method A is based on ion association complex formation of the drug with Methylene Blue . Method B is based on the charge transfer complexation reaction between Celecoxib and iodine. The absorption spectrum of Celecoxib – methylene blue and Celecoxib –iodine reaction products showed absorption peaks at 665 and 511 nm respectively. The systems obeyed the Beer’s law in the range 0.2–1µg/ml for both the methods A and B. The correlation coefficients and the limits of assays detection values were found to be 0.999, 0.37 for (method A) and 0.998, 0.426 for (method B). , respectively. Proposed methods were successfully applied to the quantitative determination of celecoxib in pharmaceutical dosage forms with good accuracy.